2004
DOI: 10.1038/sj.onc.1208179
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive role of a 2.4 Mb 9q33–q34 critical region and DEC1 in esophageal squamous cell carcinoma

Abstract: The key genes involved in the development of esophageal squamous cell carcinoma (ESCC) remain to be elucidated. Previous studies indicate extensive genomic alterations occur on chromosome 9 in ESCC. Using a monochromosome transfer approach, this study provides functional evidence and narrows down the critical region (CR) responsible for chromosome 9 tumor suppressing activity to a 2.4 Mb region mapping to 9q33-q34 between markers D9S1798 and D9S61. Interestingly, a high prevalence of allelic loss in this CR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 40 publications
5
46
0
Order By: Relevance
“…It is of note that 21 tumour-suppressor genes map within either the specific or the consistently altered regions. TIMP3 and PTEN have already been reported as tumour suppressors in thyroid tumours (Hu et al, 2006;Hou et al, 2007;Wang et al, 2007), while others are involved in a variety of different tumour types, for example, TGFBR3 and ANXA7 in prostate cancer (Torosyan et al, 2006;Dong et al, 2007), TNFSF15 and TUSC1 in lung cancer (Shan et al, 2004;Hou et al, 2005), SYK and Net1 in breast cancer (Repana et al, 2006;Huang et al, 2007), SLIT1, RSU1 and KLF6 in gliomas and glioblastosmas (Chunduru et al, 2002;Dickinson et al, 2004;Camacho-Vanegas et al, 2007), DBC1 in bladder cancer (Louhelainen et al, 2006), DEC1 in oesophageal squamous cell carcinomas (Yang et al, 2005), RB1 in retinoblastoma (Corson and Gallie, 2007) and LATS2 and DLEU7 in leukaemias (Hammarsund et al, 2004;Jimenez-Velasco et al, 2005). Some of these tumour suppressors have influence on the regulation of chromatin acetylation …”
Section: Discussionmentioning
confidence: 99%
“…It is of note that 21 tumour-suppressor genes map within either the specific or the consistently altered regions. TIMP3 and PTEN have already been reported as tumour suppressors in thyroid tumours (Hu et al, 2006;Hou et al, 2007;Wang et al, 2007), while others are involved in a variety of different tumour types, for example, TGFBR3 and ANXA7 in prostate cancer (Torosyan et al, 2006;Dong et al, 2007), TNFSF15 and TUSC1 in lung cancer (Shan et al, 2004;Hou et al, 2005), SYK and Net1 in breast cancer (Repana et al, 2006;Huang et al, 2007), SLIT1, RSU1 and KLF6 in gliomas and glioblastosmas (Chunduru et al, 2002;Dickinson et al, 2004;Camacho-Vanegas et al, 2007), DBC1 in bladder cancer (Louhelainen et al, 2006), DEC1 in oesophageal squamous cell carcinomas (Yang et al, 2005), RB1 in retinoblastoma (Corson and Gallie, 2007) and LATS2 and DLEU7 in leukaemias (Hammarsund et al, 2004;Jimenez-Velasco et al, 2005). Some of these tumour suppressors have influence on the regulation of chromatin acetylation …”
Section: Discussionmentioning
confidence: 99%
“…Several CRs in chromosome 3 were previously reported for other cancers including the 3p21.3 and 3p21.2-p14 regions in renal cell carcinoma (Yang et al, 2001), 3p21.3 in nasopharyngeal carcinoma (NPC) (Cheng et al, 1998), and 3p21.3, 3p25, and 3p13 in oral squamous cell carcinoma (Uzawa et al, 1998). Our lab recently identified 9q33-34 and 14q32 as CRs for tumorigenic suppression in ESCC Yang et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…A mouse A9 donor cell containing a single intact (MCH903.1) or truncated (MCH910.7 and MCH924.4) human chromosome 3 was transferred to the recipient, SLMT-1 cell line, as described previously (Goyette et al, 1992;Ko et al, 2005;Yang et al, 2005). The MCHs were selected in culture medium containing 500 mg/ml geneticin and hypoxanthine/aminopterin/thymidine (HAT) (Sigma, St Louis, MO, USA) for 4 weeks.…”
Section: Microcell-mediated Chromosome Transfermentioning
confidence: 99%
“…The presence of the extra chromosome 13 in the MCHs was verified by FISH using WCP 13 SpectrumGreen chromosome 13 -specific probes (Vysis). FISH and image capture were done, as previously described (11). A minimum of 20 metaphase spreads was analyzed.…”
Section: Dna Extraction Slot Blot Hybridization and Fishmentioning
confidence: 99%
“…Our previous studies identified tumor-suppressive regions localized to 3p14 (10), 9q33-34 (11), and 14q32 (12) in the ESCC cell line SLMT-1. This present study examines the tumor-suppressive role of chromosome 13 in SLMT-1.…”
Section: Introductionmentioning
confidence: 99%